Sosialisasi Teknik Dasar Pukulan pada Permainan Bulutangkis di SMK Negeri Kecamatan Biau - Said, Hariadi (Jambura Arena Pengabdian, 2023)
Badminton is a sport that uses racquets in a game that is played by two people or four people with positions in different fields of the field which are bounded by a net (net). Two people for the singles game category, and for four people for the doubles and mixed game categories. The aim of the game of badminton is to try to drop the shuttlecock in the opponent's playing area and try so that the opponent cannot hit the shuttlecock in the opponent's playing area and try so that the opponent cannot hit the shuttlecock and drop it in his own playing area. The basic techniques of badminton sports must be studied first so that when playing they can do the basic techniques well so that they can support athletes to win from the techniques they do. Because one of the determinants of victory in a match is determined by mastering the basic techniques of playing in badminton games.